2018
DOI: 10.12659/msm.905509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,25-Dihydroxyvitamin D3 on the Prevention of Chronic Obstructive Pulmonary Disease (COPD) in Rats Exposed to Air Pollutant Particles Less than 2.5 Micrometers in Diameter (PM2.5)

Abstract: BackgroundThis study aimed to investigate the effects of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) on airway changes in chronic obstructive pulmonary disease (COPD) rats exposed to air pollutant particles less than 2.5 micrometers in diameter (PM2.5), and to evaluate the mechanisms.Material/MethodsThree groups were included in this study: a normal group, a COPD model group, and a COPD with 1,25(OH)2D3 treatment group. In each group, the rats were divided into four subgroups: control and different doses of PM2.5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…A phase 2 clinical experimental study showed that inhibiting JNK reduced pulmonary fibrosis in patients ( 20 ). As previously reported, the activation of NF-κB ( 21 ) and inflammatory factor secretion mediated by PM2.5 ( 22 ) could be blocked by a JNK inhibitor, and Wnt5a suppression abrogated the PM2.5-mediated increase in inflammatory cytokines in HBECs. We further demonstrated that PM2.5 increased the levels of phosphorylated JNK and NF-κB, resulting in inflammatory factor secretion and collagen production by ASMCs, which was contrary to the application effect of BOX5 (a specific Wnt5a antagonist) or Wnt5a siRNA.…”
Section: Discussionsupporting
confidence: 62%
“…A phase 2 clinical experimental study showed that inhibiting JNK reduced pulmonary fibrosis in patients ( 20 ). As previously reported, the activation of NF-κB ( 21 ) and inflammatory factor secretion mediated by PM2.5 ( 22 ) could be blocked by a JNK inhibitor, and Wnt5a suppression abrogated the PM2.5-mediated increase in inflammatory cytokines in HBECs. We further demonstrated that PM2.5 increased the levels of phosphorylated JNK and NF-κB, resulting in inflammatory factor secretion and collagen production by ASMCs, which was contrary to the application effect of BOX5 (a specific Wnt5a antagonist) or Wnt5a siRNA.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, vitamin D has been of interest for the potential treatment and prevention of various diseases, such as chronic kidney disease and cystic fibrosis ( 65-67 ). In a previous in vivo study, vitamin D3 supplementation was found to alleviate lung injury in rats with COPD whilst also reducing cell apoptosis in the lung tissues ( 68 ). Clinical studies have also shown that vitamin D3 supplementation can alleviate moderate or severe COPD to reduce the incidence of upper respiratory tract infections ( 23-69 ).…”
Section: Discussionmentioning
confidence: 96%
“…Epidemiological and genetic risk factors for COPD include long-term smoking, persistent exposure to air pollution, respiratory infections, inhalation of biofuel smoke and occupational dust ( 24 ). Among them, smoking is a pivotal risk factor, significantly contributing to the development of COPD, thus increasing the rate of impaired lung function ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%